The Comparison between Male and Female Students in Reading Comprehension Achievement at the Third Semester of TBI STAIN Pamekasan - Kimsiyatur Rahmawati; S. Sumihatul Ummah (PANYONARA: Journal of English Education, 2020)
The students of STAIN Pamekasan consist of male and female students. Each of them shows different abilities. Male students generally have a good performance on spatial tasks and mathematical achievement. While, female students are superior in some aspects such as mathematic calculation, vocabulary, found an idea, memorizing, and making a relation, several verbal skills, reading, and writing. This study examines to know the different achievements between male and female students in reading comprehension in the third semester of TBI STAIN Pamekasan and to measure the statistically significant difference between male and female students in reading comprehension achievement at the third semester of TBI STAIN Pamekasan. This research is designed with ex-post facto. The population is 210 students, and 82 students were chosen as sample. The research instruments were tests and documentation. The quantitative data will be analyzed using a t-test. The result showed that there is no difference between male and female students in reading comprehension achievement in the third semester of TBI STAIN Pamekasan. t-value is lower than t-table [-1,226 <2,64 (1%)] [1,226 <1,99 (5%)]. Based on the result above, the lecturer needs to pay attention more to the students’ improvement in studying English, especially in reading comprehension